2019
DOI: 10.1136/neurintsurg-2018-014485
|View full text |Cite
|
Sign up to set email alerts
|

Transradial versus transfemoral access for anterior circulation mechanical thrombectomy: comparison of technical and clinical outcomes

Abstract: BackgroundA transradial approach (TRA) is associated with fewer access site complications than a transfemoral technique (TFA).However, there is concern that performing mechanical thrombectomy (MT) via TRA may lead to longer revascularization times and thus worse outcomes. Nonetheless, TRA may confer added benefits in MT since navigation of challenging aortic arch and carotid anatomy is often facilitated by a right radial artery trajectory.ObjectiveTo compare outcomes in patients who underwent MT via TRA versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 18 publications
1
81
1
1
Order By: Relevance
“…The authors have no experience with transradial approaches for stroke, though we are aware of series describing success in both the anterior and posterior circulations. 27,28 Prospective study of patients with anatomy that may prove more difficult to access via a transfemoral route using such alternative methods would benefit the community.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have no experience with transradial approaches for stroke, though we are aware of series describing success in both the anterior and posterior circulations. 27,28 Prospective study of patients with anatomy that may prove more difficult to access via a transfemoral route using such alternative methods would benefit the community.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Chen et al has demonstrated equivalence in efficacy and efficiency between trans-radial and trans-femoral approach for mechanical thrombectomy in anterior circulation stroke,20 and there are reports in the literature of success through the trans-radial approach when a trans-femoral approach has failed 16. Trans-radial is preferred over trans-brachial as the puncture site is easily compressible.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 51 patients with challenging vascular anatomy who underwent mechanical thrombectomy for anterior circulation large vessel occlusions, there were no significant differences in technical outcome and efficacy between the transradial and transfemoral groups 8. There were also no complications associated with radial artery access 8. The decision to switch from the femoral to the radial approach has been reported to take nearly 2 hours in an early report, which illustrated that radial was feasible but that alternate access sites need to be contemplated earlier in the procedural course 7.…”
Section: Discussionmentioning
confidence: 95%
“…The transradial approach is a feasible alternative when unfavorable iliofemoral or aortic anatomy is noted 7. In a retrospective review of 51 patients with challenging vascular anatomy who underwent mechanical thrombectomy for anterior circulation large vessel occlusions, there were no significant differences in technical outcome and efficacy between the transradial and transfemoral groups 8. There were also no complications associated with radial artery access 8.…”
Section: Discussionmentioning
confidence: 99%